Changes in the urinary proteome of rats after short-term intake of magnesium L-threonate(MgT) - Shen, Ziyun; Yang, Minhui; Wang, Haitong; Liu, Yuqing; Gao, Youhe (Frontiers in Nutrition, 2023)
Introduction Magnesium (Mg) is an important mineral in living organisms. Magnesium has multiple functions in the human body, wherein it plays an important therapeutic and preventive role in a variety of diseases. Methods Urine samples of rats before and after gavage of magnesium L-threonate (MgT) were collected, and the urinary proteome was identified using the LC-MS/MS technique and analyzed using various databases. Results and discussion The results illustrated that the urinary proteome of rats was significantly altered after short-term intake of magnesium supplements and that the differential proteins and the biological functions were related to magnesium. This study innovatively establishes a method to study nutrients from the perspective of urine proteomics. This work demonstrates that the urinary proteome is capable of reflecting the effects of nutrient intake on the organism in a more systematic and comprehensive manner and has the potential to provide clues for clinical nutrition research and practice.